Managing Environmental Risk Through Insurance - Freeman, Paul K.; Kunreuther, Howard (Studies in Risk and Uncertainty, 1997)
Can insurance be used as a means to obtain compliance with environmental policy? Answering this question requires examination of a broad mosaic of academic issues, including current systems available for providing compensation and deterrence, use of contracts (including insurance) as substitutes for tort law, limitations of regulatory policy-making by government agencies, pre-conditions for creation of insurance products, and market mechanisms necessary for insurance to be purchased or sold. The purpose of Managing Environmental Risk Through Insurance is to highlight the potential role that insurance and performance standards can play in managing environmental risk. Insurance can play a significant role in dealing with one of the most problematic issues facing society today - how to compensate for environmental exposures. This book analyzes the ability of insurance to play a role in managing environmental risk. It begins by outlining the role insurance plays in society in contrast to other societal tools for addressing risk: government benefit programs and imposition of involuntary liability using the court system. By so doing, the book describes the comparative advantages of insurance. The book then analyzes the insurability of the risks. Finally, the book applies the insurability analysis to three concrete environmental examples